Rents to Riches? The Political Economy of Natural Resource-led Development - Barma, Naazneen H. (World Bank, 2012)
This volume emphasizes instead the notion of 'good fit,' taking the position that welfare-promoting policies, institutions, and governance must be tailored, at least in part, to a country's specific context. In this vein, the volume presents an analytical framework for assessing a country's political economy and institutional environment as it relates to natural resource management and, on that basis, it offers a substantial set of targeted prescriptions across the natural resource value chain that are technically sound and compatible with the identified underlying incentives. In other words, the objective of this book is to help development practitioners unravel the political economy dynamics surrounding natural resource management in order to complement their technically grounded engagement. To this end, the analytical approach has been two-pronged. First, case studies were conducted on the political economy of the hydrocarbon and mineral value chains in 13 countries in the Africa, East Asia and Pacific, and Latin America and the Caribbean regions. Second, in light of this empirical material, the book highlights the current frontier of applied political economy analysis on resource dependence. This volume synthesizes the empirical and the theoretical with an emphasis on illuminating the implications for operational engagement in resource-dependent settings.